Rootless existence: A case report of internal resorption - Shrikant Subhash Dusane; Kanchan Rajesh Raikwar; Bhushan Ramdas Bhagat; Rajendra Kumar Suryavanshi (Wolters Kluwer Medknow Publications, 2018)
Internal resorption is a relatively rare resorption of dentine, which starts in the pulpal cavity either in the pulpal chamber or in the root canal and destroys surrounding dental hard tissues. The initiating factor in internal root resorption is thought to be trauma or chronic pulpal inflammation, but other etiological factors have also been suggested. In this article, we report a rare case of complete root resorption of maxillary anteriors in a 23-year-old female patient.